2021
DOI: 10.1038/s41368-021-00114-8
|View full text |Cite
|
Sign up to set email alerts
|

USP34 regulates tooth root morphogenesis by stabilizing NFIC

Abstract: Tooth root morphogenesis involves two biological processes, root elongation and dentinogenesis, which are guaranteed by downgrowth of Hertwig’s epithelial root sheath (HERS) and normal odontoblast differentiation. Ubiquitin-dependent protein degradation has been reported to precisely regulate various physiological processes, while its role in tooth development is still elusive. Here we show ubiquitin-specific protease 34 (USP34) plays a pivotal role in root formation. Deletion of Usp34 in dental mesenchymal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…We separated the protein by using 8% or 10% SDS–polyacrylamide gels and transferred it to PVDF membranes by a wet transfer apparatus (Bio-Rad). The membranes were blotted with 5% milk or bovine serum albumin (BSA) for 1 h and then incubated with primary antibodies at 4 °C overnight ( 70 ). The following antibodies were used: rabbit anti-ALKBH1 (1:2000, ab128895, Abcam), rabbit anti-HIF-1α (1:1000, ER1802-41, Huabio, Boston), rabbit anti-GYS1 (1:1000, ET1611-59, Huabio), rabbit anti-VEGF (1:2000, ET1604-28, Huabio), rabbit anti-GLUT1 (1:2000, ET1601-10, Huabio), rabbit anti-LDHA (1:2000, ET1608-57, Huabio), rabbit anti-CEBPA (1:2000, ET1612-46, Huabio), rabbit anti-FABP4 (1:2000, ET1703-98, Huabio), mouse anti-α-tubulin (1:2,000, sc-32293; Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We separated the protein by using 8% or 10% SDS–polyacrylamide gels and transferred it to PVDF membranes by a wet transfer apparatus (Bio-Rad). The membranes were blotted with 5% milk or bovine serum albumin (BSA) for 1 h and then incubated with primary antibodies at 4 °C overnight ( 70 ). The following antibodies were used: rabbit anti-ALKBH1 (1:2000, ab128895, Abcam), rabbit anti-HIF-1α (1:1000, ER1802-41, Huabio, Boston), rabbit anti-GYS1 (1:1000, ET1611-59, Huabio), rabbit anti-VEGF (1:2000, ET1604-28, Huabio), rabbit anti-GLUT1 (1:2000, ET1601-10, Huabio), rabbit anti-LDHA (1:2000, ET1608-57, Huabio), rabbit anti-CEBPA (1:2000, ET1612-46, Huabio), rabbit anti-FABP4 (1:2000, ET1703-98, Huabio), mouse anti-α-tubulin (1:2,000, sc-32293; Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…We separated the protein by using 8% or 10% SDS-polyacrylamide gels and transferred it to PVDF membranes by a wet transfer apparatus (Bio-Rad). The membranes were blotted with 5% milk or bovine serum albumin (BSA) for 1 h and then incubated with primary antibodies at 4℃ overnight [70]. The following antibodies were used: rabbit anti-ALKBH1 (1:2000, ab128895, Abcam, Cambridge, MA), rabbit anti-HIF-1α…”
Section: Western Blotmentioning
confidence: 99%
“…Deubiquitination can reverse the process of ubiquitination, by which deubiquitinases remove ubiquitin from ubiquitin-modified proteins [ 141 ]. Conditional deletion of USP34 in the dental mesenchyme cells disturbed deubiquitination-mediated NFIC stability, thus frustrating the odontogenic potential of DPCs, and a short root anomaly was observed in USP34 deletion mice [ 142 ]. USP49 was newly identified as a deubiquitinating enzyme of two transcription factors responsible for hypodontia and oligodontia, paired box gene 9 (PAX9) and Msh Homeobox 1 (MSX1), to stabilize their protein levels.…”
Section: Nedd4 E3 Ligases and Toothmentioning
confidence: 99%
“…The numerous possible causes for tooth sensitivity include worn tooth enamel and exposed tooth root surface, among others. Shuang Jiang et al reported the USP34-deficient dental pulp cells (DPCs) exhibit decreased odontogenic differentiation with downregulation of nuclear factor I/C (NFIC) and Overexpression of NFIC partially restores the impaired odontogenic potential of DPCs [ 107 ]. They reported that ubiquitin-specific protease 34 (USP34) plays a pivotal role in tooth root formation; findings indicate that USP34-dependent deubiquitination is critical for root morphogenesis by stabilizing NFIC [ 107 ].…”
Section: Ubiquitination and Deubiquitination In Oral Diseasementioning
confidence: 99%